Research trend of technology innovation from 1971 to 2024: A bibliometric analysis - Mohamad Dasuki, Norhafizah; Fauzan; Jumbri, Isma Addi; Atan, Nur Atika (Human Resource Management Academic Research Society, 2024)
Purpose – The aim of this paper is to present a detailed analysis of the Technology Innovation literature published in the Scopus database from 1971 to 2024, determining the trends in the field of technology innovation and its maturity as an academic field of study. Design/methodology/approach – Employing a quantitative approach for literature review, namely bibliometric analysis, pertinent papers were sourced from the Scopus database accessed on October 4, 2024. A total of 1,742 publications were found and analysed for bibliometric purposes. We used BiblioMagika, VOSviewer, and Publish or Perish software for data analysis. Open Refine was utilised for data cleansing. Findings – The study identified a significant increase in scientific investigations of technology innovation in recent years, along with greater collaboration and international research. A few nations, notably China, the United States, and the United Kingdom, dominate technology innovation research, but institutional and individual research output is more uniformly dispersed. It also discovered that authors or institutions predominate in the literature on technological innovation. Research limitations/implications – This study exclusively utilizes the Scopus database, concentrating on article types, journal document sources, and literature published in English. Originality/value – This paper provides significant contributions. Initially, it highlights the growing research tendency in the domain of technological innovation. Secondly, it assesses the present maturity of the field according to its epistemological framework, concludes that technological innovation is progressively maturing, and fosters a growing consensus within the domain of study.